Hydraulic erosion mitigation in sandy soil using cation-crosslinked gelation biopolymer - Lee, Minhyeong; Chang, Ilhan; Cho, Gye Chun (Acta Geotechnica, 2025)
The increasing frequency of geotechnical disasters and climate-related land degradation underscores the need of resilient soil erosion mitigation. This study investigates the effectiveness of Cr3+-crosslinked xanthan gum (CrXG), a cation-crosslinked gelation biopolymer with time-dependent gelation and water-resistant properties, in mitigating hydraulic soil erosion. Through the erosion function apparatus test, rheological analysis, and microscopic observations, results indicate notable improvements in soil erosion resistance with CrXG treatment, elucidating distinct reinforcing mechanisms attributable to the gel state of the biopolymer hydrogel. The addition of 0.25% CrXG to the soil mass significantly improves critical shear stress and critical velocity, reducing the erodibility coefficient by four order magnitudes compared to untreated sand. Within 48 h, the transition from a viscous to rigid gel state in CrXG, driven by cation crosslinking, transforms the soil from high (II) to low (IV) erodibility class. Scour predictions using the program, based on river hydrograph conditions, indicate a substantial delay in reaching a 1-m scour depth. This study highlights CrXG-soil composite’s potential as an advanced geomaterial for mitigating geohazards such as floods and stream scouring, while offering insights into its competitiveness with conventional soil stabilization techniques.
Keywords: Chemical crosslinking; Erosion; Erosion function apparatus; Sand; Scouring; Xanthan gum biopolymer